ASSOCIATION OF NDUFC2 POLYMORPHIC VARIANTS WITH LEFT VENTRICULAR HYPERTROPHY IN HUMAN HYPERTENSION. (June 2022) - Gallo, Giovanna; Forte, Maurizio; Tocci, Giuliano; Cotugno, Maria; Marchitti, Simona; Stanzione, Rosita; Bianchi, Franca; Palmerio, Silvia; Sciarretta, Sebastiano; Volpe, Massimo; Rubattu, Speranza
Abstract : Objective: Previous experimental studies showed that a dysfunction of the NADH dehydrogenase (ubiquinone), the mitochondrial Complex I (CI), is associated with the development of left ventricular hypertrophy (LVH). A deficiency of Ndufc2 (a subunit of CI) impairs CI activity and causes severe mitochondrial dysfunction. The NDUFC2/rs11237379 polymorphic variant is associated with reduced gene expression and impaired mitochondrial function, contributing to increased susceptibility to vascular diseases. We examined the association of NDUFC2/rs11237379 and another NDUFC2 polymorphic variant (rs641836) with the development of LVH in hypertensive patients. Design and method: Two-hundred-fourty-six hypertensive subjects (147 male, 59.7%) with a mean age of 59 ± 15 years were studied. Seventy-nine individuals (32%) presented LVH. Results: The association analysis for both SNPs showed that hypertensive patients carrying the TT genotype at the NDUFC2/rs11237379 had a significant increase of echocardiographically assessed septal thickness (p = 0.001), posterior wall thickness (p = 0.003), relative wall thickness (RWT) (p = 0.01), LV mass/ body surface area (BSA) (p = 0.012) and LV mass/height2.(p = 0.0033) compared to subjects carrying either CC or CT genotypes. To better dissect the genetic effect, a covariate ANOVA was performed for each cardiac variable, considering age, gender, body mass index (BMI), office blood pressure (BP), antihypertensive treatment with a combination of 2 or more drugs and the number of BP-lowering agents as covariates. The adjustment for covariates revealed significant differences for septal thickness (p = 0.07), posterior wall thickness (p = 0.008), RWT (p = 0.021), LV mass/BSA (p = 0.03). With regard to NDUFC2/rs641836, hypertensive subjects carrying the mutant A allele had a significant increase of septal thickness (p = 0.001), posterior wall thickness (p = 0.001), RWT (p = 0.005), LV mass (p = 0.001), LV mass/BSA(p = 0.001), LV mass/height2.7(p = 0.002) compared to wild-type homozygotes. After adjustment for covariates, the results were significant for septal thickness (p = 0.017), posterior wall thickness (p = 0.011), LV mass (p = 0.003), LV mass/BSA (p = 0.002) and LV mass/height2.7(p = 0.010). Conclusions: Our results demonstrate for the first time a significant association of NDUFC2 variants with LVH in hypertensives and highlight a novel role of CI dependent mitochondrial dysfunction on increased susceptibility to cardiac damage in human hypertension. This study paves the way of a new pathophysiological mechanism of LVH which may lead to new clinical strategies.